Differences of room temperature vulcanized silicone and dimensional accuracy towards silicone PVS light body impression: Study experimental - Kambolong, Sitti Annisa; Masyhudi, Masyhudi; Sulistiani, Dewi Arsih; Asfirizal, Verry; Irsal, Imran; Sukotjo, Cortino (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRAKIntroduction: Dental impressions are materials used to accurately replicate. Silicon Room Temperature Vulcanized (RTV) impression material is known to have good ultimate tensile strength and flexibility. Polyvinyl siloxane light body impression (low viscosity) which has the same viscosity as RTV material. Dimensional accuracy is used to see the accuracy of the impression material. Objective to investigate the optimal ratio of base, catalyst, and filler for RTV silicone to achieve the setting time and working time. To investigate is a difference between treatments using fillers and not using fillers. To investigate the difference in dimensional accuracy between the two materials. Methods: This research is pure experimental researches with randomized post-test only control group design. The control group was PVS light body silicone and the treatment group was RTV silicone. RTV silicones were categorized into 6 treatment groups. The treatments were increasing the amount of catalyst and adding talc filler. Each treatment group had 4 replications. Based on data analysis, there was no difference in the average. Results: The results showed that RTV silicone had significant difference with p < 0.05. At the ratio of RTV treatment groups without fillers by using fillers had a real difference with p < 0.05. In terms of dimensional accuracy, RTV silicone and silicone with light body impression viscosity did not have significant difference with p > 0.05. Conclusion: The optimal ratio for RTV silicon is 10:2 with the addition of 10 grams of talc filler. In the treatment using filler and without filler, having original fabrics with faster results was found in the filler treatment group. There is no significant difference in dimensional accuracy between RTV silicone and silicone with light body impression viscosity, so that both materials have the same accuracy.KEY WORDS: Room temperature vulcanized (RTV) silicone, light body impression, dimensional accuracyPerbandingan silikon room temperature vulcanized dan akurasi dimensi terhadap silikon PVS light body impression dalam kedokteran gigi : studi eksperimentalABSTRAKPendahuluan: cetakan gigi adalah bahan yang digunakan untuk membuat replika atau tiruan yang akurat. Bahan cetak Silicon Room Temperature Vulcanized (RTV) diketahui memiliki ultimate tensile strength serta kelenturan yang baik. Bahan polyvinyl siloxane (PVS) light body (viskositas rendah) yang memiliki viskositas sama dengan bahan RTV. Akurasi dimensi digunakan untuk melihat keakuratan bahan cetak. Metode: Penelitian ini bermetode eksperimental murni dengan desain penelitian Randomized post-test only control group design. Kelompok kontrol adalah Silikon PVS light body dan kelompok perlakuan adalah Silikon RTV. Silikon RTV dikelompokkan menjadi 6 kelompok perlakuan, dengan perlakuan menaikkan jumlah katalis dan penambahan filler talc. Setiap kelompok perlakuan dilakukan pengulangan sebanyak 4 kali. Akurasi dimensi dari silikon RTV dilakukan pengecoran, dan diukur menggunakan dental caliper. Pengulangan dilakukan sebanyak 4 kali. Berdasarkan analisis data didapatkan tidak terdapat perbedaan rata-rata. Hasil: Hasil penelitian menunjukkan bahwa silikon RTV dengan PVS light body memiliki perbedaan yang nyata dengan nilai p<0.05. Pada akurasi dimensi antara kedua bahan silikon RTV dengan silikon PVS berviskositas light body impression, tidak memiliki perbedaan yang nyata dengan nilai p>0.05. Simpulan: RTV didapatkan rasio perbandingan yang paling optimal adalah katalis dan base (2:10) dengan penambahan filler talc sebanyak 10 gram. Pada akurasi dimensi silikon RTV dengan silikon berviskositas light body impression tidak memiliki perbedaan yang nyata/signifikan, sehingga kedua bahan memiliki keakuratan yang sama.KATA KUNCI: Silikon room temperature vulcanized (RTV), light body impression, akurasi dimensi